2017
DOI: 10.1016/j.pcd.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a general practitioner-led integrated model of care on the cost of potentially preventable diabetes-related hospitalisations

Abstract: The differences in hospitalisations attributable to better integrated primary/secondary care can yield large cost savings. Models such as the Beacon are highly relevant to current national health care reform initiatives to improve the continuity and efficiency of care for those with complex chronic disease in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Of the included studies, 20 examined populations with a specific chronic illness and two studied multiple chronic conditions [22,27]. The most common disease type was diabetes with 12 of the 22 studies examining populations with the diabetes [18,23,26,30,31,[33][34][35][36][37][38][39]. Five studies examined patients with COPD [20,21,24,25,29], two examined patients with Parkinson's disease [19][20][21][22][23][24][25][26][27][28] and one study examined patients with cancer [32].…”
Section: Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the included studies, 20 examined populations with a specific chronic illness and two studied multiple chronic conditions [22,27]. The most common disease type was diabetes with 12 of the 22 studies examining populations with the diabetes [18,23,26,30,31,[33][34][35][36][37][38][39]. Five studies examined patients with COPD [20,21,24,25,29], two examined patients with Parkinson's disease [19][20][21][22][23][24][25][26][27][28] and one study examined patients with cancer [32].…”
Section: Populationmentioning
confidence: 99%
“…That is, the teams consisted of professionals suited to managing the health conditions which they sought to address. Many teams had either a GP leading [18,30,39] or a nurse coordinating care [28]. For most part, studies documenting multidisciplinary teams also demonstrated that regular meetings and/or remote contact between team members working in primary and secondary care services can be effective in terms of ensuring swift transitions between care levels, thus enhancing patient safety and continuity of care.…”
Section: Intervention Studiedmentioning
confidence: 99%
See 1 more Smart Citation
“…Quite a few teams were only made up of nurses and community health workers, sometimes including primary care physicians or pharmacists rather than multidisciplinary teams [15,16,19]. Even for multidisciplinary team management, the central role was usually played by primary care physicians or specialists instead of nurses [20][21][22]. Furthermore, the duration of follow-up was usually less than one year, long-term effects of nurse-led multidisciplinary team were scarce [19,23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, not all the phases of care require the same level of expertise or have the same level of complexity [12]. Recently, many healthcare systems have adopted a model of integrated care involving specialists in the most critical phases and for more complicated patients, while GPs take care of the routine management of the disease in less complex cases [9,13,14]. In this context, evidence on the effectiveness of shared care is growing [15,16].…”
Section: Introductionmentioning
confidence: 99%